DIETARY INTERVENTIONS IN YOUNG FEMALE GYMNASTS EFFECTS ON BODY COMPOSITION, HORMONAL HEALTH, AND PERFORMANCE - FangJinlin (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Young female gymnasts are exposed to high training loads and strict aesthetic demands, placing them at increased risk of low energy availability (LEA), inadequate nutrition, and related physiological dysfunctions. Recent research has focused on dietary interventions to improve body composition, hormonal health, and athletic performance in this population. Current evidence suggests that chronic energy deficiency is strongly associated with hypothalamic–pituitary–gonadal axis disruption, menstrual irregularities, and impaired bone health. Inappropriate dietary restriction may also reduce lean mass and impair metabolic efficiency. Interventions such as increased caloric intake, individualized macronutrient planning, and nutrition education have shown benefits in restoring hormonal balance and improving physiological outcomes. Adequate carbohydrate and protein intake are particularly important for recovery, training capacity, and performance adaptation. However, longitudinal and adolescent-specific research remains limited. Future studies should emphasize individualized nutrition strategies and multidisciplinary approaches. Overall, evidence-based dietary interventions are essential for balancing athletic performance with long-term health in young female gymnasts.